Determinants of obesity among adults aged 35 to 65 years attending Ssekanyonyi Health Centre IV, Mityana District. A cross-sectional study. - Nakubulwa, Suzan; Nansereko, Hasifa; Nalubega, Jane Frank; Naggulu Posperia, Immaculate; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David (Student’s Journal of Health Research Africa, 2025)
Background In Uganda, the prevalence of obesity among adults has been steadily increasing, reaching an estimated prevalence of 29% in urban areas and 14.3% in rural settings. The purpose of the study was to assess the determinants of obesity among adults aged 35 to 65 years attending Ssekanyonyi Health Centre IV in Mityana District. Methods A descriptive cross-sectional study design was used employing quantitative methods of data collection and was conducted in Ssekanyonyi Health Centre IV. In 4 days, 33 adults were selected using a simple sampling method. A structured questionnaire was used to collect data, and it involved closed-ended questions. The data collected was analyzed manually, and the findings were entered into Microsoft Excel 2013, which was then presented in the form of tables, pie-charts, and graphs. Results Out of 33 participants, 30.3% were aged 45-49 years, and more than half (58%) were females. For individual determinants, over half (64%) were rarely exercising, more than half (55%) were taking sugary drinks daily, and 85% overate when stressed. Concerning health facility determinants, more than half (58%) health workers could sometimes support them in addressing their weight management issues, all (100%) didn’t have weight management programs and (52%) could wait for a very long time and socio-cultural determinants, (64%) large body size was perceived as a sign of wealth and (94%) had a family history of obesity. Conclusion Obesity among adults was driven by poor lifestyle choices, limited healthcare support, cultural perceptions, and genetic predisposition; hence, the need for clear interventions. Recommendation Promote regular physical activity, reduce sugary drink intake, establish accessible weight management programs, educate communities on healthy body image, and improve health facility support services.